Expressive syntax matters for second-order false belief: a study with hearing-impaired children - Serrat, Elisabet; Amadó, Anna; Durrleman, Stephanie; Intxaustegi, Alaitz; Sidera, Francesc (Frontiers in Communication, 2024)
While children with typical language development may capitalize on general language skills to grasp the content of others' minds, those with challenges in mind-reading could rather rely more specifically on complementation structures. However, most studies investigating mind-reading have focused on first-order false-belief reasoning, while much less is known about second-order false-belief, particularly for children that may present language difficulties, such as children with hearing impairment.This study aims to explore the link between language development and second-order false-belief in hearing-impaired children compared to their hearing counterparts. It seeks to ascertain whether mastering second-order false-belief requires the comprehension of complements or other language skills in hearing-impaired children, and if a distinct pattern emerges in their hearing peers.Children with hearing-impairment (n = 22) and a chronological age-matched control group (n = 25), ages 8-12, were administered a second-order false-belief task (carefully avoiding use of complements and highly visual). Alongside this, they completed assessments of expressive vocabulary, receptive and expressive syntax, recalling sentences, and a recursive sentential complements task.Correlational analysis revealed that in the control group only productive syntax was related to performance on the second-order false-belief task, while in the hearingimpaired group, expressive vocabulary, recalling sentences and sentential complements were related to second-order false-belief performance.These results show that vocabulary, recursive complements and expressive syntax are particularly important aspects for second-order false-belief success in children with hearing-impairment as compared to their hearing peers. These results shed light on how language and second-order false-belief understanding are related in their development.